Bugis ethnic perception towards urgency of political decentralization and district autonomy in South Sulawesi, Indonesia - Yakub, Andi; Abdul Ghani, Ahmad Bashawir; Anwar, Mohammad Syafi’i (Gupta Publications, 2018)
Bugis ethnic is one of the ethnics in Indonesia and it is the major ethnic in South Sulawesi province. Political decentralization and district autonomy that is carried out in South Sulawesi aims to establish harmony and national unity in a condition of diverse community (pluralism) including creating equal development through the people’s empowerment. The research applies qualitative method through in-depth interview with key informants from formal (Bupati and bureaucrats) and non-formal (politicians, religious leaders, traditional leaders and intellectuals) elite figures. Results of the research found that majority of Bugis ethnic have a revisionist style of thinking instead of conservative/orthodox and pragmatic. Revisionist means the Bugis ethnic views power decentralization and broader authority as possible actions to be carried out smoothly in a district by observing the local values and local wisdom. Also, changes in political decentralization model that is based on local wisdom values can be carried out in stages along with the spirit of national unity and joint development for community’s prosperity.